Basic Cycle in Dentistry Students’ Training: The Gap in the Integration of Knowledge and Social Reality - Luiz Roberto Augusto Noro; Bárbara Cássia de Santana Farias-Santos; Pedro Henrique Sette-de-Souza; Isabel Alves Gomes Pinheiro; Raul Elton Araújo Borges; Rayanne Karina Silva Cruz; Rosiane Viana Zuza Diniz (Revista Electrónica de Investigación Educativa, 2018)
One of the main premises of the Dentistry curricular guidelines is the integration of knowledge, bringing together the basic, clinical and public health areas. The aim of this research was to understand how the contents of the “basic cycle” contribute to dentists’ academic training. A qualitative study was performed, and developed through interviews of focal groups consisting of students from 2nd to 4th semester. The analysis produced five categories: decontextualization of social sciences, curricular structure, the gap between the basic and professional cycles, student resignation to the “basic cycle”, and teachers at the core of the process. It was concluded that the dichotomy between the basic and professional cycles complicates curricular integration and compromises students' commitment to their graduation. As a result, it is necessary to incorporate the principles provided in the Dentistry curricular guidelines, such as students’ proactive behavior towards the learning process and the teacher's role as a facilitator.